Artificial intelligence and AI Act: from the individual to the algorithm? - Tesi, Francesca; Gasparri, Wladimiro (Zbornik radova Pravnog fakulteta u Novom Sadu, 2025)
This paper focuses on the analysis of the AI Act as a risk-based regulatory model for AI aimed at balancing the need for technological development, which can ensure greater efficiency and well-being, with the protection of fundamental rights, for which potential risks must be identified along with appropriate mitigation measures. The goal is to prevent a public decision being left solely to the ‘thinking machine’, an expression of a mechanism of indifferentiation that, through mathematical-computational logic, flattens individual identities (social complexity) onto data, no matter how numerous.
Keywords: artificial intelligence, AI Act, public administration, rule of law